Gene flow on insect‑resistant genetically modified maize - Nascimento, Vivian Elias; Von Pinho, Édila Vilela de Resende; Von Pinho, Renzo Garcia; Souza, João Cândido de; Nascimento Júnior, André Domingos do (Pesquisa Agropecuaria Brasileira, 2012)
<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The objective of this work was to estimate the gene flow on insect‑<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">resistant transgenic maize in grain production fields. Grain samples were collected in fields containing conventional and transgenic maize in the Brazilian municipalities of: Itumirim, Uberlândia, Paracatu, and Tupaciguara, in Minas Gerais State; Itapetininga and Pedrinhas, in São Paulo State; and Assaí and Ponta‑<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Grossa, in Paraná State. Seed samples were collected in conventional maize crops starting 5 m away from the transgenic maize source. Ten corn cobs were collected from individual plants per sampling point, with four replicates, totaling 40 corn cobs at each evaluated distance. Gene flow analyses were carried out by real‑<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">time polymerase chain reaction (PCR). On average, 82% of cross‑<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">fertilization occurred within the first 30 m. The highest outcrossing rates were observed in Itapetininga, SP, – at rates above 10% up to a distance of 50 m; however, less than 1% at 100 m distance. The 20-m isolation, with ten border lines, is not sufficient to ensure outcrossing rates lower than 1%.